PENGARUH PROMOSI KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI DAN PERILAKUTIDAK AMAN DI PT.CINTA RAJA SERDANG BEDAGAI - Luci Riani Br Ginting; Delita Br Panjaitan; Febriyanta . (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
The use of Personal Protective Equipment (PPE) many factors that cause workers are not compliant to use PPE, even though the company has provided PPE and implementing regulations that require workers to use PPE. Companies must also create workforce compliance to use PPE. The most basic stage to foster workforce awareness so that compliance with PPE is by establishing a safety culture using PPE. This type of research is experimental. The study design was a quasy experiment with a time series design approach. The study design was a pre-experimental (One group pre and post test design) that is a study that used a group of subjects, measurements were carried out before and after treatment. This study uses a non-probability sampling method, which is a sampling method where only certain individuals or objects in a population are selected as samples. The sampling technique in this study is total sampling, which is a sampling technique where the number of samples is equal to the population. Based on the results of statistical tests using paired sample t-test with a confidence level of 95% (Î± = 0.05) obtained p value = 0,000 â‰¤ 0.05, meaning that there is an effect of K3 promotion on the use of personal protective equipment at PT. Cinta Raja in 2020. It is hoped that PT. Cinta Raja should pay attention to its employees in using personal protective equipment to minimize work accidents.